2000
DOI: 10.19182/remvt.9709
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation pathologique chez des poulets du virus vélogénique de la maladie Newcastle isolé chez une pintade

Abstract: Une bande de 160 coquelets Harco âgés de six semaines ont été inoculés par voie intramusculaire avec un isolat nigérian local de virus vélogénique de la maladie de Newcastle (VMN) obtenu à partir d'une pintade morte. Des signes cliniques de la maladie, principalement la dépression, des diarrhées verdâtres, la paralysie, l'opisthotonos et le torticolis, ont pu être observés sur les volailles trois jours après l'inoculation. Le taux de morbidité a été de 100 p. 100 alors que celui de mortalité a été de 92 p. 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…Following this was greenish diarrhea, which is an indication of gastrointestinal lesion. This is also in agreement with what has been described by Okoye et al (2000) and Hamid et al (1991). Severe nervous signs were observed prominent of which were ataxia, paralysis and torticollis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Following this was greenish diarrhea, which is an indication of gastrointestinal lesion. This is also in agreement with what has been described by Okoye et al (2000) and Hamid et al (1991). Severe nervous signs were observed prominent of which were ataxia, paralysis and torticollis.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the incubation period of experimental ND was three days, which is in agreement with the report of Okoye et al (2000). Hamid et al (1991) reported an incubation period of 2 to 16 days.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations